Innovation policies in Brazil during the 2000s: The need for new paths - Fernanda De Negri; Andre Tortato Rauen (Institute for Applied Economic Research (ipea), 2018)
This paper intends to discuss the road ahead for the Brazilian innovation policies. To do so, it provides an overview of the several new policies adopted in Brazil in the last decade to foster technology and innovaton. Based on a broad review of Brazilian literature on evaluation of innovation policies, the document also presents the main achievements and outcomes of these policies as well as those that we consider to be their main misunderstandings. Finally, a range of policy challenges that have arisen as a result of efforts to encourage innovation in the Brazilian economy, and also presents some recommendations for overcoming them.
Keywords: O31; O38; 330; innovation policies; Brazil; evaluation